N‐Bridged Acyclic Trimeric Poly‐Cyclodiphosphazanes: Highly Tuneable Cyclodiphosphazane Building Blocks. (25th September 2020) - Shi, Xiaoyan; León, Felix; Sim, Ying; Quek, Shina; Hum, Gavin; Khoo, Yi Xin Joycelyn; Ng, Zi Xuan; Par, Mian Yang; Ong, How Chee; Singh, Varun K.; Ganguly, Rakesh; Clegg, Jack K.; et al.
Abstract: We have synthesized a completely new family of acyclic trimeric cyclodiphosphazane compounds comprising NH, N i Pr, N t Bu and NPh bridging groups. In addition, the first NH‐bridged acyclic dimeric cyclophosphazane has been produced. The trimeric species display highly tuneable characteristics so that the distance between the terminal N(H)R moieties can be readily modulated by the steric bulk present in the bridging groups (ranging from ≈6 to ≈10 Å). Moreover, these species exhibit pronounced topological changes when a weak non‐bonding NH⋅⋅⋅π aryl interaction is introduced. Finally, the NH‐bridged chloride binding affinities have been calculated and benchmarked along with the existing experimental data available for monomeric cyclodiphosphazanes. Our results underscore these species as promising hydrogen bond donors for supramolecular host–guest applications. Abstract : We have synthesized a completely new family of acyclic trimeric cyclodiphosphazane compounds comprising NH, N i Pr, N t Bu and NPh bridging groups. These species possess both a highly tuneable intra‐terminal N(H)R moiety distance that can be readily modulated by varying the steric bulk of the bridging groups, in addition to topological flexibility upon incorporation of weak non‐bonding interactions.